Relationship between Early Inflammatory Response and Clinical Evolution of the Severe Multiorgan Failure in Mechanical Circulatory Support-Treated Patients. (14th July 2014) - Caruso, Raffaele; Campolo, Jonica; Verde, Alessandro; Botta, Luca; Cozzi, Lorena; Parolini, Marina; Milazzo, Filippo; Nonini, Sandra; Martinelli, Luigi; Paino, Roberto; Marraccini, Paolo; Frigerio, Maria
Abstract : Background . The mechanical circulatory support (MCS) is an effective treatment in critically ill patients with end-stage heart failure (ESHF) that, however, may cause a severe multiorgan failure syndrome (MOFS) in these subjects. The impact of altered inflammatory response, associated to MOFS, on clinical evolution of MCS postimplantation patients has not been yet clarified. Methods . Circulating cytokines, adhesion molecules, and a marker of monocyte activation (neopterin) were determined in 53 MCS-treated patients, at preimplant and until 2 weeks. MOFS was evaluated by total sequential organ failure assessment score (tSOFA). Results . During MCS treatment, 32 patients experienced moderate MOFS (tSOFA < 11; A group), while 21 patients experienced severe MOFS (tSOFA ≥ 11) with favorable (B group) or adverse (n = 13, C group) outcomes. At preimplant, higher values of left ventricular ejection fraction (LVEF) and estimated glomerular filtration rate (eGFR) were the only parameter independently associated with A group. In C group, during the first postoperative week, high levels of interleukin-8 (IL-8) and tumor necrosis factor (TNF)- α, and an increase of neopterin and adhesion molecules, precede tSOFA worsening and exitus. Conclusions . The MCS patients of C group show an excessive release to IL-8 and TNF- α, and monocyte-endothelial activation after surgery, that might contribute to the unfavourable evolution of severe MOFS.